2010
DOI: 10.1007/s00442-010-1782-2
|View full text |Cite
|
Sign up to set email alerts
|

Geographic host use variability and host range evolutionary dynamics in the phytophagous insect Apagomerella versicolor (Cerambycidae)

Abstract: The high diversity of phytophagous insects has been explained by the tendency of the group towards specialization; however, generalism may be advantageous in some environments. The cerambycid Apagomerella versicolor exhibits intraspecific geographical variation in host use. In northern Argentina it is highly specialized on the herb Pluchea sagittalis (Asteraceae), while in central and southern areas it uses seven Asteraceae species. To study host species geographical variation from ecological and evolutionary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…However, the Asclepias cardenolides do suppress the rootfeeding larvae and the advantage of Tetraopes may in fact be its ability to escape competition in a plant inaccessible to other herbivores rather than the acquired protection of adults, which is doubt ful (see above). The supposedly conspe cific allopatric populations of widely distributed species often have more or less different (though usually overlapping) regional host associations; those differences can only be partly explained by the lack of potential hosts in certain regions (e.g., Logarzo et al 2011). More studies, such as that by Michaud & Grant (2005) (who found individuals of Dectes texanus LeConte developing in soybean and sunflower biologically compat ible although strongly differing in average mass), are needed to clarify whether, and at what rate, we may encounter host races or sympatric cryp tic hostspecific species.…”
Section: Cerambycidae Latreille 1802mentioning
confidence: 99%
“…However, the Asclepias cardenolides do suppress the rootfeeding larvae and the advantage of Tetraopes may in fact be its ability to escape competition in a plant inaccessible to other herbivores rather than the acquired protection of adults, which is doubt ful (see above). The supposedly conspe cific allopatric populations of widely distributed species often have more or less different (though usually overlapping) regional host associations; those differences can only be partly explained by the lack of potential hosts in certain regions (e.g., Logarzo et al 2011). More studies, such as that by Michaud & Grant (2005) (who found individuals of Dectes texanus LeConte developing in soybean and sunflower biologically compat ible although strongly differing in average mass), are needed to clarify whether, and at what rate, we may encounter host races or sympatric cryp tic hostspecific species.…”
Section: Cerambycidae Latreille 1802mentioning
confidence: 99%
“…We report here two traits, body size and longevity, supporting this hypothesis in the case of the seed beetle Megacerus eulophus . Other studies have not found evidence of host availability influencing local host adaptation in the seed beetle Stator limbatus [7], [8] and in the stem borer Apagomerella versicolor [52].…”
Section: Discussionmentioning
confidence: 89%
“…While numerous phytophagous insects are specialists, some pest species have secondary resource plants that can provide some refuge (Logarzo et al, 2011). This would lower the negative effect pest individuals experience due to Bt individuals.…”
Section: Discussionmentioning
confidence: 98%